Efektifitas Edugame Interaktif Nearpod Terhadap Retansi Belajar siswa kelas XI IPA SMAN 1 Kecamatan Tujuh Belas - Nurmailia, Emi; Qurbaniah, Mahwar; Mukti Rahayu, Hanum (Universitas Muhammadiyah Sorong, 2024)
Effective learning media is needed to overcome the low retention of student learning on respiratory system materials in humans. One of the media that can be used is Nearpod Interactive Edugame . This study aims to determine the difference, influence, and magnitude of the effectiveness of nearpod interactive edugame on student learning retention. The research method used is Quasi Experimental Design with Nonequivalent Control Group Design. Sempel determination using simple random sampling, class XI IPA 1 as experimental class and XI IPA 2 as control class. Treatment in the experimental class using Nearpod Interactive Edugame and control class using LKPD. Data collection techniques use measurement techniques and direct observation. Retention data collection tool with retest tests, posttest questions, and retests. The average retention value of the experimental class was 78.85 while the average retention value of the control class was 65.6. The significance of the Whitney retention U-Mann Test results was 0.005 (0.005<0.05). The result of the retention effect size obtained is 1.03 so that the criterion of the magnitude of the effect size is 55,4%%. Based on this, it can be concluded that there are significant differences in student retention and have an influence on the retention of students taught with Nearpod Interactive Edugame media.